2023
DOI: 10.3390/jcm12072664
|View full text |Cite
|
Sign up to set email alerts
|

Decompression with or without Fusion for Lumbar Synovial Cysts—A Systematic Review and Meta-Analysis

Abstract: The management of symptomatic lumbar synovial cysts (LSC) is still a matter of debate. Previous systematic reviews did not stratify data according to different treatment techniques or incompletely reported comparative data on patients treated with lumbar posterior decompression (LPD) and lumbar decompression and fusion (LDF). The aim of our study was to compare LPD and LDF via a systematic review and meta-analysis of the existing literature. The design of this study was in accordance with the 2020 Preferred Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…Page et al ( 30 ) reported a predictive model for lumbar synovial cyst recurrence following decompression without fusion and found some predictive factors of recurrence, including a facet inclination angle of >45°, canal stenosis of >50%, T2 joint space hyperintensity, and the presence of grade I spondylolisthesis. One systematic review and meta-analysis showed that decompression combined with fusion was associated with better results in terms of lower postoperative back pain and cyst recurrence compared with decompression alone; however, there were no differences in the reoperation and complication rates ( 31 ). None of the patients in this study experienced recurrence or reoperation during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Page et al ( 30 ) reported a predictive model for lumbar synovial cyst recurrence following decompression without fusion and found some predictive factors of recurrence, including a facet inclination angle of >45°, canal stenosis of >50%, T2 joint space hyperintensity, and the presence of grade I spondylolisthesis. One systematic review and meta-analysis showed that decompression combined with fusion was associated with better results in terms of lower postoperative back pain and cyst recurrence compared with decompression alone; however, there were no differences in the reoperation and complication rates ( 31 ). None of the patients in this study experienced recurrence or reoperation during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Benato [1] J 1]. [10] e 1 of 15 patients with LSC were typically older, exhibited significant degenerative facet disease, and developed larger and more anteriorly located LSC more likely to be associated with radicular pain.…”
Section: Conclusion Outcomesmentioning
confidence: 99%
“…Five studies showed that patients with LSC/Stenosis undergoing primary decompressions/fusions resulted in lower LSC recurrence rates vs. for those having decompressions alone [ Table 1 ]. [ 1 , 7 , 9 , 14 , 16 ] Utilizing 4 databases (i.e., 17 studies; 824 patients), Ramhmdani et al . (2019) found that patients with LSC/Stenosis/DS were; “...more likely to undergo spinal fusion surgery than laminectomy alone compared with patients with LSC and no preoperative DS” [ Table 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, as a strategy for lumbar spine surgery, the etiology and pathophysiology of the disease are first inferred [ 1 , 16 ], and the extent of the surgery is then determined based on spinal canal stenosis, the presence or absence of bony unions such as DISH [ 7 ], and the morphology of the fracture [ 17 ] based on image analysis [ 4 , 5 , 7 ]. Next, after selecting minimally invasive surgery [ 10 ], microendoscopic surgery [ 9 , 10 ], or conventional surgery as the surgical method, appropriate spinal instruments and cages [ 18 ] are selected.…”
mentioning
confidence: 99%